Novel Frontiers of Advanced Neuroimaging - Fountas, Kostas N. (IntechOpen, 2013)
Emerging imaging modalities continuously increase the diagnostic sensitivity and accuracy of neuroimaging, and have transformed diagnostic radiology into a powerful research and clinical tool. Various novel neuroimaging modalities have become of paramount importance, not only in establishing diagnosis but also in guiding surgical intervention, and in evaluating the treatment effect. Advanced MR based techniques such as Fractional Anisotropy, Diffusion Tensor Imaging, Proton Spectroscopy, and task-generated as well as resting-state functional MRI have tremendously increased the power of the modern neuroscientist's armamentarium. The employment of advanced neuroimaging techniques have been expanded in the scientific fields of neuropsychology, consumer's psychology, and forensic medicine. Our current textbook presents exactly a collection of such innovative work, and explores new frontiers, and future applications of neuroimaging